Universalism vs. Traditionalism – different rationality, different anthropologies - Kopeć-Kaczor, Anna (Hybris, 2020)
The article presents thesis (claimed by Alasdair MacIntyre) that arguing about the meaning of such notions as 'identity', 'subjectivity', 'freedom' is unsolvable. These conflicts are based on a wrong concept that there is only one true rationality. MacIntyre confronts such concept (universalism) with that one which admits that there are many different types of rationalities (rooted in different traditions). The first part of the article shows his (MacIntyre) understanding of universality and tradition. The second focuses on such notions as identity and freedom developed in two traditions, liberlism and virtue ethics. In the end it presents the conclusion that the factor which distinguishes these two traditions is the fact of existing (not existing) goods of excellence.